Crosstalk between C/EBP homologous protein (CHOP) and glucocorticoid receptor in lung cancer. (15th November 2016) - Mihailidou, Chrysovalantou; Panagiotou, Christina; Kiaris, Hippokratis; Kassi, Eva; Moutsatsou, Paraskevi
Abstract: Loss of homeostasis triggers the endoplasmic reticulum (ER) stress response and activates the unfolded protein response (UPR) resulting in the induction of the CCAAT/enhancer binding protein (C/EBP) homologous protein (CHOP). Glucocorticoids (GCs), via the glucocorticoid receptor (GR), regulate numerous physiological processes in an effort to maintain homeostasis. Previous studies demonstrated that glucocorticoids suppress ER stress by enhancing correct folding of secreted proteins and degradation of misfolded proteins. Here, we describe a novel crosstalk between ER-stress and the glucocorticoid receptor signaling. We showed that treatment of wild type mice with Tunicamycin (inducer of ER-stress) increased GR protein levels in the lungs. Treatment of A549 cells (human lung cancer cells) with ER stress inducers modulated the Dexamethasone-induced subcellular localization of GR and the phosphorylated forms of GR (pGRSer211 and pGRSer203) with concomitant changes in the expression of primary GR-target genes. We demonstrated a significant protein-protein interaction between GR and CHOP, (GR-CHOP heterocomplex formation) under ER stress conditions. The functional consequences of ER stress- GR signaling crosstalk were assessed and demonstrated that long time exposure (24–48 h) of A549 cells to dexamethasone (10 −6 M) reversed the Tunicamycin-induced cell death, a phenomenon associated with parallel increases in GR protein content, increases in cell survival parameters and decreases in cell apoptosis-related parameters. Our study provides evidence that there is a cross talk between ER-stress and GR signaling, this being associated with mutual functional antagonism between CHOP and GR-mediated pathways in lung cells with important implications in lung cell function. Highlights: ER-stress increased GR levels in vivo and in vitro. ER-stressors affect GR phosphorylation and GR nuclear-cytosolic trafficking. ER-stress modulates GR –dependent gene expression. Protein-protein interaction between GR and CHOP. DEX reverses TUN induced cell death in a GR dependent manner.